1,1

This is solution of transcendental equation: (-1 + x^2)^(1/x) (2/(-1 + x^2) - Log[ -1 + x^2]/x^2) + (1 + x^2)^(1/x) (2/(1 + x^2) - Log[1 + x^2]/x^2)=0.

Table of n, a(n) for n=1..105.

Constant k=2.752343784...

(PARI) solve(x=2, 3, (-1 + x^2)^(1/x) * (2/(-1 + x^2) - log( -1 + x^2)/x^2) + (1 + x^2)^(1/x) * (2/(1 + x^2) - log(1 + x^2)/x^2)) \\ Michel Marcus, Sep 09 2013

Sequence in context: A201319 A110945 A197571 * A296564 A266262 A105387

Adjacent sequences: A178419 A178420 A178421 * A178423 A178424 A178425

cons,nonn

Artur Jasinski, May 27 2010

approved